The Reality of Services Provided to the Gifted in Saudi Universities from the Students’ Point of View - Abu Nasser, Fathi; AlAli, Rommel; Aboud, Yousra; Saleh, Shoeb (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Attention to young gifted has become a necessity for active participation in meeting the future needs of the kingdom, which justifies talent development and personality building programs, attracting gifted and creative students, and following them up within the university’s specializations in proportion to their abilities. The study focused on the reality of the services of caring for gifted students at King Faisal University from the perspective of students. A sample of (310) undergraduate students, including (232) females, during the academic year 2020/2021. The descriptive analytical method was used. The Reality of Services offered to Gifted Students scale was applied (Cronbach Alpha= 0.93). The results of the study showed a medium degree of services provided in five dimensions (Curriculum and courses, characteristics and competencies, enrichment activities, Create a database, exchange of experiences), and the (infrastructure and equipment) dimension came with a high degree, The results also showed a high predictive ability of the variable (Care) in the level of services provided more than other variables. The study recommended the need to increase attention to the infrastructure of services provided at the university in the fields of study.